2011
DOI: 10.1007/128_2011_215
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Residual Dipolar Coupling in Studying Proteins by NMR

Abstract: The development of residual dipolar coupling (RDC) in protein NMR spectroscopy, over a decade ago, has become a useful and almost routine tool for accurate protein solution structure determination. RDCs provide orientation information of magnetic dipole–dipole interaction vectors within a common reference frame. Its measurement requires a nonisotropic orientation, through a direct or indirect magnetic field alignment, of the protein in solution. There has been recent progress in the developments of alignment m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
102
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(106 citation statements)
references
References 89 publications
1
102
0
1
Order By: Relevance
“…This analysis showed that POTRA1 and POTRA2 have similar D a and R values (Table 1), where the D a values for POTRA1 showed a bimodal distribution, due to the degeneracy of D a (Figure 4a). This degeneracy leads to ± D a having the same fit to the RDC data when two of the axes in the tensor have the same magnitudes, which occurs at both R = 0 and R = 2/3 (Chen and Tjandra, 2012). As seen in Table 1, the bimodal distributions generally occur for R values close to the maximum of 2/3.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This analysis showed that POTRA1 and POTRA2 have similar D a and R values (Table 1), where the D a values for POTRA1 showed a bimodal distribution, due to the degeneracy of D a (Figure 4a). This degeneracy leads to ± D a having the same fit to the RDC data when two of the axes in the tensor have the same magnitudes, which occurs at both R = 0 and R = 2/3 (Chen and Tjandra, 2012). As seen in Table 1, the bimodal distributions generally occur for R values close to the maximum of 2/3.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the differences in D a and R for the POTRA1–2 and POTRA4–5 subdomains in the Pf1 alignment medium provide strong evidence for flexibility between these subdomains. The timescale (frequency) of this flexibility in the RDC analysis is less than the magnitude of the RDC themselves, which have a frequency of ≈10 Hz; therefore, corresponding to timescales faster than 100 ms (Chen and Tjandra, 2012). The alignment tensors were also determined from RDCs in 3% C12E5/hexanol alignment medium and compared to the Pf1 data had somewhat larger errors due to lower signal-to-noise in the experimental data and more of the POTRA domains had bimodal distributions (Table 1 and Figure 4b).…”
Section: Resultsmentioning
confidence: 99%
“…from picoseconds to hours 517 . To prevent undue repetition of the same theoretical concepts, the present report neither aims to offer a comprehensive overview of these NMR methodologies, nor to fully cover the wide array of protein systems exemplifying the importance of conformational flexibility in protein function.…”
Section: Introductionmentioning
confidence: 99%
“…Certain subsets of isotopically labeled amino acids are relatively inexpensive, making application to glycoproteins economical, and the reduction in numbers of resonances increases resolution for larger proteins (Goto and Kay 2000; Kainosho et al 2006; Prestegard et al 2014). Even with fewer labeled sites chemical shift perturbation can provide information on ligand binding or protein-protein association (Williamson 2014), and residual dipolar couplings (RDCs) can constrain relative orientation of structural units in multiple domain proteins or protein-protein complexes (Chen and Tjandra 2012; Lipsitz and Tjandra 2004). The only prerequisite is the replacement of triple resonance assignment methods with an alternative strategy.…”
Section: Introductionmentioning
confidence: 99%